The Use of Social Media in an Islamic Perspective Online Trading Business (Case Study of Mas Joko's Food stalls Jl. Sultan Alauddin, Tamalate District During the Covid-19 Pandemic) - Muchran, Muchriady; Wahyuni, Sri; Wahyuni, Nur (Universitas Muhammadiyah Makassar, 2022)
This study aims to determine the Islamic perspective on the use of social media in online buying and selling businesses, to determine the impact of online marketing in the Covid-19 era faced by Mas Joko's food stall business. This research is a field research using qualitative methods. Data collection was done by interview, observation, and documentation. The results show that the Islamic perspective on the use of social media in online buying and selling, that online buying and selling is based on the Qur'an where online buying and selling is a form of muamalah, in this case honesty in sharia economic transactions is a very important part. Where a trader must be honest, based on the desire for other people to get goodness and happiness such as by explaining the defective condition of a merchandise that he knows and which is not visible to the buyer so that sales in buying and selling transactions are carried out online. has fulfilled the contract (agreement). Sales made online are very helpful for Mas Joko's food stall income during the Covid-19 pandemic. The impact of online marketing in the Covid-19 era faced by Mas Joko's food stall business decreased by around 70% due to a lack of visitors due to the closing of campuses close to the stalls.